2020
DOI: 10.1002/jsfa.10953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different thawing methods on the efficiency and quality attributes of frozen red radish

Abstract: BACKGROUND:The thawing process is regarded as an essential step before the consumption of frozen foods. This study aimed to evaluate the possibility of ultrasound thawing of frozen red radish and to explore the characteristics of ultrasound thawing. The influence of low-frequency ultrasound (LFU) on the thawing efficiency of frozen red radish cylinders in air and water mediums was investigated. The effects of different ways of thawing, including air thawing (AT), water thawing (WT), refrigeration thawing (RT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…This was expected because the air had lower heat conductivity and specific heat than water. Similar results were also found on frozen red radish [ 30 ] and frozen strawberries [ 25 ]. When microwave thawing was performed with 100 W, the thawing time was approximately 3 min.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This was expected because the air had lower heat conductivity and specific heat than water. Similar results were also found on frozen red radish [ 30 ] and frozen strawberries [ 25 ]. When microwave thawing was performed with 100 W, the thawing time was approximately 3 min.…”
Section: Resultssupporting
confidence: 84%
“…During the thawing process, the interior ice crystals of frozen food would stepwise transfer to the water. Certain amounts of water may be absorbed and held by the cells, while the left part of the unabsorbed water would exude from the cells, causing liquid loss [ 30 ]. Both water and water-soluble materials that leaked from cells during the thawing process were included in the drip loss [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…A US-assisted water thawing process was also applied to red radishes [190] . It was indicated that the low-frequency US was an efficient method to ease the thawing process and maintain the product's structure, vitamin C, and color.…”
Section: Ultrasonication Applications On Color Profile Of Foodsmentioning
confidence: 99%
“…The frequency of the former ranges over 1 MHz, which is mainly used for food non-destructive testing, quality evaluation, and process control to ensure the quality and safety of food. The frequency of the latter ranges from 18 to 100 kHz, which is mainly used in food processing, such as extraction [46] , enzymolysis of protein [11] , modification of starch [14] , sterilization [47] , inactivation of enzymes [48] , washing [49] , [50] , osmotic dehydration [13] , freezing [51] , [52] and thawing [53] .…”
Section: Background Of Ultrasoundmentioning
confidence: 99%